Construction of a reconfigurable DNA nanocage for encapsulating a TMV disk. Issue 61 (10th July 2019) - Zhang, Tianran; Zeng, Xiangzhi; Guan, Shuwen; Li, Xiumei; Qu, Zhiyu; Qin, Luyao; Hou, Chunxi; Liu, Junqiu
Abstract : A new reconfigurable DNA nanocage based on a DNA origami method has been constructed to capture a tobacco mosaic virus (TMV) disk. Abstract : A new reconfigurable DNA nanocage based on a DNA origami method has been constructed to capture a tobacco mosaic virus (TMV) disk. We used a hairpin to control the transformation of the nanocage and a strand of TMV RNA to attract the TMV disk. Our design could inspire new DNA–protein complex designs.